2015
DOI: 10.1021/acs.jafc.5b03474
|View full text |Cite
|
Sign up to set email alerts
|

Phenylethanoid Glycoside Profiles and Antioxidant Activities of Osmanthus fragrans Lour. Flowers by UPLC/PDA/MS and Simulated Digestion Model

Abstract: Variations of phenylethanoid glycoside profiles and antioxidant activities in Osmanthus fragrans flowers through the digestive tract were evaluated by a simulated digestion model and UPLC/PDA/MS. Major phenylethanoid glycosides and phenolic acids, namely, salidroside, acteoside, isoacteoside, chlorogenic acid, and caffeic acid, were identified in four cultivars of O. fragrans flowers, and the concentration of acteoside was the highest, being up to 71.79 mg/g dry weight. After simulated digestion, total phenyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…The extracts were analysed by UPLC (ACQUITY, Waters, Milford, MA, USA) equipped with a photodiode array (PDA) detector (ACQUITY) and MS (Synapt G2, Waters, Milford, MA, USA), using a modification of method described by Jiang et al (2015). A BEH-C18 Symmetry column (100 mm × 2.1 mm; 1.7 μm) attached with a VanGuard precolumn (2.1 mm × 5 mm, 1.7 μm) (Waters, Milford, MA, USA) was maintained at 40°C.…”
Section: Uplc-pda and Qtof-ms Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…The extracts were analysed by UPLC (ACQUITY, Waters, Milford, MA, USA) equipped with a photodiode array (PDA) detector (ACQUITY) and MS (Synapt G2, Waters, Milford, MA, USA), using a modification of method described by Jiang et al (2015). A BEH-C18 Symmetry column (100 mm × 2.1 mm; 1.7 μm) attached with a VanGuard precolumn (2.1 mm × 5 mm, 1.7 μm) (Waters, Milford, MA, USA) was maintained at 40°C.…”
Section: Uplc-pda and Qtof-ms Analysesmentioning
confidence: 99%
“…The MS detector was operated in the electrospray ionisation (ESI) negative mode targeting phenolic compounds, which were the main biological compounds in O. fragrans flowers (Xiong et al, 2014;Jiang et al, 2015), under the following conditions: capillary voltage, 2.6 kV; sampling cone voltage, 40 V; extraction cone voltage, 4.0 V; source temperature, 100°C; desolvation temperature, 300°C; cone gas flow rate, 50 L/h; and desolvation gas, 600 L/h. An MS E method was used at a scan range from m/z 50 to m/z 1000.…”
Section: Uplc-pda and Qtof-ms Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Osmanthus fragrans Lour., O. fragrans, commonly referred to as sweet osmanthus, is a plant species widely cultivated in Eastern Asia that is well known for the very distinct and pleasant fragrance of its flowers. 1,2 O. fragrans is of high economic value in China. 2,3 The highly distinct floral fragrance of O. fragrans has been the subject of extensive research.…”
Section: Introductionmentioning
confidence: 99%
“…10 Literature showed that phenylethanoid glycosides are found mainly in Orobanchaceae plants 12,13 and possess different pharmacological properties, including anti-inammatory, antioxidant, antitumor, antiviral, antibacterial, immunomodulatory, and neuroprotective effects. [14][15][16][17][18][19][20][21] Protective effects against UVB-induced phototoxicity are related to plant extracts which are rich in antioxidants. 22,23 The purpose of this study is to assess the inhibitory activity against UVB-induced phototoxicity and its underlying mechanisms of total phenylethanoid glycosides (TPG) and magnoloside I a (MI a ) from M. officinalis var.…”
Section: 6mentioning
confidence: 99%